Desarrollo e implantación de un sistema de ubicación geográfico para la gestión de personal (oficiales, clases y policías), vehículo y repuestos en la Policía Nacional de Loja Nro. 7. - González Alulima, Blanca Flor (2014)
This career’s final project is focus in the analysis, design and implementation of a Geographic Location System for paperwork of personal, vehicles and spare parts of National Policy of Loja. The Geographic Location System (SUGP) is a web application where the administrator of personal and logistic offices can administrate users, polices, transfers, sanctions, retires, licenses, documents, mobile units, assignation of mobile unit, combustible order, work order, maintenance paper, products, incomes, expenditures, kardex, catalogues, and geographic location that had been realized with location of police assignation, mobile unit and spares. The location is given by geographic coordinates from base of dates that can be seen by Google Maps, and others activities of National Policy. The methodology used to develop this software is ICONIX, based in complexity of analysis of Rational Unified Processes (RUP) methodology, and practicality to develop Extreme Programming (XP) methodology. The objective of this methodology is to cover the whole cycle of project. The SUGP was implemented in Java, with the JBoss Seam 5.1.0 applications server that has a MCV (model, view and controller) development pattern, and MySqll 5.6, as base manager.